Smoking and COVID-19: A Scoping Review. (February 2021) - Haddad, Chadia; Bou Malhab, Sandrella; Sacre, Hala; Salameh, Pascale
Smoking affects a person's overall health and damages nearly every organ of the body. Since smoking tobacco affects and damages the lungs, it increases the risk of respiratory infections and makes it easier for the coronavirus disease (COVID-19) to invade the lung tissue, causing more severe symptoms and increasing the risk of death. However, debates are still ongoing as to the effect of cigarette smoking on vulnerability to COVID-19. Some studies, where active smokers were underrepresented among patients with COVID-19, claimed that a "smoker's paradox" may exist in COVID-19 and that smokers are protected from infection and severe complications of COVID-19. However, other studies reported the opposite trend. The objective of this study is to review the findings of epidemiological and in vitro studies about the association between smoking and the risk of contracting COVID-19, taking into account disease severity. Several epidemiological studies have found a higher smoking prevalence among COVID-19 infected patients. Also, studies had shown that people with respiratory diseases caused by tobacco use are at higher risk of developing severe COVID-19 symptoms. Studies have shown that in vitro, the acute exposure allows for more severe proximal airway epithelial disease from SARS-CoV-2 by reducing the mucosal innate immune response and the proliferation of airway basal stem cells and has implications for disease spread and severity in people exposed to cigarette smoke, with a more severe viral infection and cell death. Smoker patients with different comorbidities are at higher risk of contracting the COVID-19 virus and have a worse prognosis for the virus as well as for their comorbidities. Further investigations of the interaction between smoking and COVID-19 are warranted to accurately assess the risk of contracting COVID-19 among smokers, and the progression to mechanical ventilation or death in patients who suffer from it.